STRATEGIC PLANNING OF SUSTAINABLE TOURISM DEVELOPMENT: INTERNATIONAL EXPERIENCE AND RECOMMENDATIONS FOR UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
The article is devoted to the analysis of strategic approaches to the sustainable development of tourism based on international experience. Institutional management models, environmental practices, forms of community participation, as well as the implementation of sustainability standards (GSTC, CST, etc.) in various countries are considered. Special attention is paid to assessing the current state of the tourism industry in Uzbekistan using the SWOT analysis method. Based on the identified strengths and weaknesses, as well as taking into account international practices, recommendations have been formulated for the development of a national strategy for sustainable tourism focused on institutional development, regional specifics and integration into international standards.